Pengembangan Instrumen Evaluasi Lembar Kerja Siswa (LKPD) untuk Meningkatkan Efektivitas Pembelajaran Bahasa Arab di SD Islam Terpadu Andalusia Parepare/ Development of Student Worksheets Evaluation Instruments (LKPD) to Improve the Effectiveness of Arabic Language Learning at Andalusia Integrated Islamic Elementary School in Parepare - Raodhatul Jannah; Nawal Sa'adah; Hastuti Indriani; Andi Muhammad Asbar (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to develop and evaluate a Student Worksheet (LKPD) for Arabic language instruction at the Integrated Islamic Elementary School (SDIT) Andalusia Parepare. The study is based on the low interest of students in learning Arabic and the absence of engaging and motivating evaluation tools. To address this issue, the research focuses on designing an LKPD that improves student involvement and comprehension through interactive and enjoyable learning activities. The research method used is development research with the 4D model (Define, Design, Develop, Disseminate), which includes needs analysis, LKPD design, development and revision based on expert input, and product testing through individual and small group trials. Validation involved content and media experts to assess the quality and appropriateness of the content and design, while the practicality was evaluated based on user feedback from Arabic classes. Results show that the developed LKPD is both valid and practical. Content experts scored the LKPD 57 out of 65 (88%), indicating a “very valid” rating, with suggestions to add clearer instructions and sample questions. Media experts rated the layout and visuals 58 out of 70 (83%), also categorized as “very valid,” and recommended enhancing images and adding an introduction section. Practicality tests by teachers scored 75 out of 80 (94%), confirming that the LKPD supports learning needs and student motivation. Overall, the findings confirm that the LKPD is feasible, effective, and appropriate for use in Arabic language instruction in elementary education settings.Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi Lembar Kerja Peserta Didik (LKPD) sebagai instrumen evaluasi dalam pembelajaran Bahasa Arab di SD Islam Terpadu (SDIT) Andalusia Parepare. Latar belakang penelitian ini adalah rendahnya minat siswa dalam belajar Bahasa Arab serta keterbatasan alat evaluasi yang mampu meningkatkan keterlibatan dan motivasi belajar. Penelitian ini menggunakan model pengembangan 4D (pendefinisian, perancangan, pengembangan, penyebaran) yang meliputi analisis kebutuhan, perancangan, pengembangan dan revisi berdasarkan validasi ahli, serta uji coba produk melalui tes individu dan kelompok kecil. Validasi dilakukan oleh ahli materi dan media untuk menilai kelayakan isi dan desain LKPD, sedangkan aspek kepraktisan diukur dari umpan balik guru dan siswa terhadap penerapan LKPD dalam pembelajaran. Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan tergolong sangat valid dan praktis, dengan skor validitas isi sebesar 88% dari ahli materi, 83% dari ahli media untuk aspek visual dan tata letak, serta skor kepraktisan sebesar 94% berdasarkan penilaian guru. Temuan ini menunjukkan bahwa LKPD mampu meningkatkan pemahaman dan motivasi siswa dalam belajar Bahasa Arab, sehingga layak dan efektif digunakan sebagai instrumen evaluasi dalam pembelajaran Bahasa Arab di jenjang sekolah dasar.